Extraction of protocatechuic acid enriched fraction from Clinacanthus nutans leaves - Zamery, Muhammad 'Izzuddin; Ab. Hadi, Hazrina; Mohd Hassan, Norazian (Malaysian Pharmaceutical Society, 2017)
INTRODUCTION: Clinacanthus nutans is abundant in Malaysia. It contains bioactive compounds such as phenolics. PCA is a phenolic acid, naturally existed in plant species including C. nutans. It has beneficial effects especially for the treatment and prevention for diseases pertinent to oxidative stress. OBJECTIVES: To extract PCA enriched fraction from C. nutans leaves, analyse it with validated high-performance liquid chromatography (HPLC) method, assess its anti-oxidant capacity. METHODS: The leaves were macerated in n-hexane followed by dichloromethane and methanol. Methanol extract was fractionated by vacuum liquid chromatography (VLC) and the fractions were screened by thin layer chromatography (TLC). The fraction was analysed by validated HPLC method. Anti-oxidant activity assay was performed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. RESULTS: 32 fractions were obtained with VLC. Four fractions (F1 – F4) were acquired after pooling similar TLC pattern. As compared to F3, F2 had been observed to possess more intense spot of PCA while F1 and F4 have no PCA spot. All parameters for HPLC method validation were within the specifications. HPLC of F2 showed PCA at 8.124 minutes retention time with the highest peak area among other compounds at 260 nm. Anti-oxidant assay showed anti-oxidant activity for F2 (IC50=898.51±10.93mg/mL) is the highest as compared to unfractionated methanol extract (IC50=1148.20±19.25mg/mL) (p=0.001) and other extracts (p<0.001). CONCLUSION: PCA enriched fraction (F2) was obtained from C. nutans leaves. F2 possesses the highest anti-oxidant among others, thus, it can be utilized in future research focuses on anti-oxidant applications.